What’s in the pipeline for open access in Sweden? Progress report from a national and institutional perspective - Eellend, Beate; Gilbert, Jonas (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. In January 2013 the Swedish Government commissioned the Swedish Research Council to develop a proposal for national guidelines for open access to scientific information, in collaboration with the National Library of Sweden. Comments from different stakeholders were collected through meetings, dialogues as well as an open web forum during 2013 and 2014. Many of the views expressed were utilized in the final document. The final proposal, which includes guidelines for both scientific publications, artistic works and research data, was submitted to the Government in January 2015. Also, the proposal contains recommendations on what needs to be further investigated and solved, in order to enable the fulfillment of the strategic objectives for 2025, when all scientific publications and artistic works resulting from research financed with public funds shall be published immediately with open access. In December 2015 the Swedish Government invited approximately 100 representatives from HEIs, funders, research and library organizations as well as researchers to a national hearing. The aim was to discuss how Sweden and the government can proceed with the transformation to an open access publishing system. During the hearing it was emphasized that the transformation to an open access publishing system in many respects is connected to the existing qualification and funding allocation system. Therefore there is a need for strong incentives for researchers to publish open access. Also, there is a national and international need to get control of both subscription fees and APCs in order to facilitate the transition to an open access publication system. At the end of 2016 the Government is expected to address the national guidelines in the Budget bill, the Research Bill as well as in different appropriation directives to national HEI’s and funders. Also, the Minister for Research and Higher Education has expressed the will to notify a national coordination task to the National Library of Sweden regarding open access to scientific publications and artistic works and a parallel coordination task to the Swedish Research Council regarding open access to research data. The Swedish Government supports the European Council Conclusions on the transition towards and Open Science System. Our proposed presentation aims to give a state of the art report of the current development, both from a national perspective and from an institutional perspective. How are we are preparing to implement the guidelines? What strategies are institutions and libraries using, both with regard to publishers and researchers? We hope to inspire a discussion and exchange of experiences, since several countries now are in a similar process.